Consumers' Perception Analysis on Service Quality of Coffee Shops and Coworking Spaces in Yogyakarta, Indonesia - Canta, Raras Inggita Arcci Citra; Kristanti, Novita Erma; Yuliando, Henry (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
Every marketing organization, whether manufacturing or service provider company is required to create differentiation, positioning, and competitive strategies. The most important factor to increase competitiveness in the field is quality of service. Therefore, providing good service appropriate to the expectations and desires of consumers is essential to create and ensure satisfaction. Tangible, reliability, responsiveness, assurance, and empathy are significantly related to consumer’s retention efforts. It is important to analyze the relationship between consumers and the product or service offered to understand that consumers have diverse desires when trying new product or service. This study aimed to investigate the priority of service attributes requiring improvements in coffee and coworking spaces, as well as provide suggestions for improvements based on observations. The variables were in the dimensions of service quality (tangible, reliability, responsiveness, assurance, and empathy). Furthermore, relevant data were collected through questionnaires, while nonprobability sampling method was adopted. Analysis method included Importance Performance Analysis (IPA) and Potential Gain in Customer Value (PGCV). The respondents were 300 consumers of K, R, and S. IPA results identified three attributes in quadrant I, which were sorted by PGCV priority. These attributes included tangible variables (4), empathy (19), and responsiveness (9). Recommendations for improvements included checking all available facilities, providing training to improve employee skills for service, and proactiveness in interaction by offering available menus.